Metabolic markers of short and long-term exogenous DL-beta-hydroxybutyrate supplementation in episodic migraine patients: an exploratory analysis of a randomized-controlled-trial - Putananickal, Niveditha; Gross, Elena C.; Orsini, Anna-Lena; Schmidt, Simone; Hafner, Patricia; Gocheva, Vanya; Nagy, Sara; Henzi, Bettina C.; Rubino, Daniela; Schädelin, Sabine; Sandor, Peter; Fischer, Dirk (Frontiers in Pharmacology, 2023)
Background:Emerging findings propose that the pathophysiology of migraine may be associated with dysfunctional metabolic mechanisms. Recent findings suggest that migraine attacks are a response to the cerebral energy deficit, and ingestion of ketone bodies stabilizes the generation of a migraine attack. Based on these findings, ketone body supplementation is postulated as a prophylactic treatment approach to restore cerebral metabolism deficiency. Metabolic markers are unexplored after exogenous ketone body supplementation in episodic migraineurs. Therefore, the present single-arm uncontrolled explorative analysis evaluated blood ketone body and glucose concentration after short and long-term 6g exogenous DL-Mg-Ca-beta-hydroxybutyrate (DL-βHB) supplementation. Methods: The presented data are part of the MigraKet randomized-control cross-over clinical trial of 41 episodic migraineurs (Number NCT03132233). Patients were given a single dose of 6g DL-βHB. Ketone body and glucose blood concentration were assessed before intake, 20 minutes, and 40 minutes after DL-βHB intake. Ketone body, glucose concentration and glycated hemoglobin values were evaluated after twelve weeks of 18g DL-βHB ingestion (total dose), taken three times daily (6g/dose;3x/day). Linear models explored the association between the ketone body and glucose levels. Results:Ketone body concentration increased within-group to a mean of 0.46 (0.30) mmol/L after 40 minutes post- DL-βHB supplementation (estimate=0.24 mmol/L, CI=[0.20,0.27],p<0.01). This within-group increase of ketone body concentration did not change after repeated daily intake of DL-βHB supplementation over twelve weeks (estimate=0.00 mmol/L, CI=[-0.03,0.04], p=0.794). DL-βHB intake significantly reduced blood glucose concentration within-group from a mean baseline of 4.91 (0.42) mmol/L to 4.75 (0.47) mmol/L 40 minutes post-DL-βHB supplementation (estimate=-0.16 mmol/L, CI=[-0.15, 0.03],p<0.01). Repeated DL-βHB supplementation for twelve weeks showed no change within-group in acute ketone bodies concentration (estimate=0.00 mmol/L,CI=[-0.03,0.04],p=0.794) and in the HbA1c value (estimate=0.02, CI=[-0.07,0.11], p=0.69). Conclusion:A single dose of 6g DL-βHB significantly elevated blood ketone bodies and decreased blood glucose concentration within-group in episodic migraineurs. Long-term DL-βHB supplementation for 12 weeks showed no effect within-group on acute ketone body concentration and had not impact on HbA1c. The elevation of the ketone body concentration was moderate, indicating that nutritional ketosis was not reached. Therefore, a dose higher than 6 g of DL-βHB is required to reach the nutritional level of ketosis.